Finger Painting dan Perkembangan Motorik Halus Anak: Studi Pra-Eksperimen di Raudhatul Athfal - Wahyuni, Ayu Tri; Sumarni, Sri (Nusantara: Jurnal Pendidikan Indonesia, 2025)
Purpose – This study aims to improve fine motor development in children aged 4-5 years through finger painting activities. Using a quantitative approach with a one-shot case study design, involving 17 children at Raudhatul Athfal Nurul Falah Baturaja.Method – Using a quantitative research design, with test instruments as the main tool for data collection. This study used a post-test to assess the improvement of fine motor skills involving 17 children at RA Nurul Falah. using the purposive sampling technique and using statistical tests with the help of SPSS, namely, the t-test, validity test, and reliability test. Findings – The results showed a significant increase in children's fine motor skills. The results of statistical tests using the t-test show a significant increase, where the t-count value of 4.08 is greater than the t-table value of 1.746, so Ho is rejected, and Ha is accepted. This finding confirms that finger painting acts as an effective sensory stimulation medium in improving children's fine motor skills. Research Implications – These findings provide empirical evidence that finger painting can be used as a neuromuscular development connection that can strengthen hand-eye coordination in early childhood. If children are involved in finger painting activities regularly, the development of small muscles in the hands and fingers will increase optimally. If finger painting is integrated into the PAUD curriculum, there will be an increase in children's readiness in writing and drawing when entering primary education.